Accommodation or confrontation? Some responses to the Eiselen commission report and the Bantu education act with special reference to the Methodist church of South Africa - Rundle, Margaret (School of Education, 2016)
This study was undertaken at a time when South African politicians and educators are facing the challenge of a major restructuring of the education system, and at a time when the the Methodist Church of South Africa is being encouraged, by some, to become more involved in the provision of education again. It focusses on the three events - the appointment of the 'Commission of Inquiry into Native Education' (usually referred to as the Eiselen Commission), the Report of that Commission, and the Bantu Education Act of 1954 which led to the introduction of the system of Bantu Education in 1955. Consideration is given to the responses of various 'liberal' and 'radical' groups to those events.